Users’ Guide to the Use of Dictionary - Ajah, Christopher Okeke (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Dictionary making is the preoccupation of a lexicographer (dictionary compiler) and the art of making it (dictionary) is called lexicography. Dictionary can either be in printing or electronic form. It is no doubt a vital tool for language learning and usage. The importance of a dictionary in learning and usage of a language cannot be neglected because its role in learning generally which includes among others: word meaning, word usage, pronunciation, spelling, origin and parts of speech are fundamental in communication. The research adopts secondary sources of data collection. The neglect of the use of dictionary for study by our students is no doubt the cause of poor language performance, low performance in examination and poor individual vocabulary acquisition. This work will therefore be limited to the features of a dictionary that will serve as a guide to dictionary users.